PENGARUH DEBT TO EQUITY RATIO DAN RETURN ON ASSET TERHADAP RETURN SAHAM PERUSAHAAN MAKANAN DAN MINUMAN INDONESIA - Candra, Revi (UNIB Press, 2019)
This study is to examine the effect of DER on stock returns, the effect of DER on ROA, the effect of ROA on stock returns, the effect of DER and ROA on stock returns and the indirect effect of DER on stock returns mediated by ROA. The research data obtained through the website of the Indonesia Stock Exchange (IDX) manufacturing companies in the food and beverage sector listed on the IDX as many as 18 companies. The method of analysis uses linear regression analysis with 4 regression models using the IBM version of the SSS program. t test shows the results of the study that DER has no effect on stock returns, DER has no effect on ROA, ROA has an effect on stock returns, and DER has no indirect effect on stock returns through ROA.